A calculation method of deposition profiles in chemical vapor deposition reactors using bio‐inspired algorithms. Issue 7 (7th May 2015) - Takahashi, Takahiro; Inagaki, Taeka; Nariai, Shingo; Kodama, Junichi; Arakawa, Masamoto; Ema, Yoshinori; Hoffmann, Patrik; Knez, Mato; Vahlas, Constantin; Alexandrov, Sergei
Abstract Estimating the predicted results of experimental data by a simulator is one of the most important processes in deciding the performance of the automatic modeling system of reaction mechanisms in chemical vapor deposition (CVD). Therefore, we developed a novel calculation method, in which robust and accurate calculations along with reduced computing cost were achieved, to reproduce deposition profiles in the specific types of reactors. In order to improve the performance of the calculation method, we developed the method by use of the novel optimization algorithms, which are biologically inspired. We adopted real‐coded genetic algorithms (GAs) and artificial bee colony (ABC) as the bio‐inspired algorithms (BIAs). Boundary value problems for estimating diffusion‐reaction equations by iterations of numerical integrations were changed into problems of finding the linear combinations consisted of a few "basis functions", which are ideally inherent in the reactors. The coefficients of the linear combinations were optimized by the BIAs. We demonstrate the improved performance of the simulator by the BIAs using the batch‐type reactor with round‐shaped substrates. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)